Uma história da disciplina matemática no Atheneu Sergipense durante a ação da reforma Francisco Campos (1938-1943) - Souza, Suely Cristina Silva (2011)
This study aims to analyze the configuration of Mathematics in Atheneu Sergipense, according to the proposals set out by the Reformation Francisco Campos, between the years 1938 and 1943 in order to clarify the implementation process in the training of students and teachers' performance that institution. The year 1938 stands out for implementing the Decree. 7, March 14, 1938, which regulated that institution, according to Reforma and Francisco Campos in 1943, marks the beginning of the inclusion of new courses, merger and extinction of new chairs. As specific objectives, the survey also aimed to: analyze the local and national education legislation in order to understand the process of implementation of reform within the Francisco Campos Atheneu Sergipense; present the faculty of the institution, explain the selection process for access the chair, the profiles of teachers of mathematics and to investigate the process of unifying the branches of mathematics, the presence of Mathematics in Elementary and Complementary courses, and discuss the performance of students in that discipline. The sources were Laws, Decrees, Regulations Institutional Official Gazette Newspapers, Minute Book, Logs, Newsletters, Book of tuition, books and theses Points contests. Thus, this dissertation used the category as a main course, through studies Chervel (1990). Other concepts have also provided valuable support as school culture, based on conceptions of Julia (2001) and Forquin (1993); field, capital (cultural, social and symbolic), according to Bourdieu (2008, 2005, 2004 and 1996) and intellectual as Sirinelli (1998). For this purpose, divided into three chapters. The first chapter dealt with the secondary school, their aims, their characteristics and performance for the second Mathematics Reform Francisco Campos, but also its implementation within the Atheneu Sergipense. The second chapter presented the faculty of the institution in its various classifications and responsibilities through analysis of local legislation in order to confirm the existence and relevance of the dictates of the Reformation Francisco Campos. Unfolded the selection process for admission to the chair of that institution, by reporting the first contest of the Chair of Mathematics and sketched the profile of mathematics teachers, disseminating their training courses provided in other positions and occupations. The third chapter delineated the configuration of the discipline and explained his presence in elementary and Complementary cycles through the courses taught, the textbooks adopted in the Basic Course and the performance of mathematics teaching in two courses As a result, conclude that learning mathematics were present over the years studied, in their different purposes and taught by a faculty legitimized. The programs in mathematics, conceived through the parts documentary, show significant changes in their subjects, but similar to the Pedro II College. Also I learned that the ideas circulated by Francisco Campos Reform Atheneu Sergipense were inserted in the inclusion of complementary courses in 1936, and subsequently regulated under the State Act, 1938. Since the mathematical lessons, even if belatedly, they followed the innovations proposed by the movement installed, responsible for training and discipline methodisation school mathematics. Thus, the work contributes mainly in research on the history of mathematics teaching in Atheneu Sergipense, little studied, but observations by some descriptive and analytical elements of the course allowed the construction of teaching math and instigate other researchers in Studies on History of Mathematics Education in Sergipe.